ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP OUTLET PEJATEN VILLAGE MALL - Viona Prameswari Farahnur, - (2019)
This research is a quantitative deskriptive research that aims to determine the effect of marketing mix on purchasing decisions. The population in this research were consumers of The Body Shop in Pejaten Village Mall. The sample size was taken by 100 respondents, with accidental sampling method. Data collection is done through questionnaires. Analytical technique used is the method of analysis PLS (Partial Least Square). The results of this study show that the product and price have no significant influence on purchasing decisions. While promotion and distribution have an influence on purchasing decisions.